Pelatihan Pembagian Harta Warisan Berdasarkan Hukum Islam di Desa Reuleut Timu Kabupaten Aceh Utara - Muhammad Hatta; Sitti Saarah Trisha; Siska Simesti Nazara; Zulfan Zulfan (Publikasi Indonesia, 2022)
Family conflicts that often occur in the community are related to the distribution of inheritance. Many of the people who cut off family relations just because of the struggle for inheritance inherited from their parents. In fact, not infrequently there are often murders between family members just because of the struggle for inheritance. The division of inheritance is considered unfair and benefits only one heir so that the other heirs feel aggrieved and file a court lawsuit or bring the problem to the village parents or the local village apparatus. Inheritance conflicts as mentioned above also occur in the village of Reuleut Timu, Muara Batu District, North Aceh Regency. This inheritance conflict is caused by the mechanism of inheritance distribution which is considered detrimental to one of the heirs or the distribution of inheritance does not provide justice for all heirs, resulting in feuds and even bloodshed between heirs. This community service program fosters and provides training to village officials on the distribution of inheritance based on Islamic law. This training increases the knowledge of village officials about the mechanism for calculating inheritance in a proper, correct manner and providing justice for all heirs so as to avoid conflicts within the family in Reuleut Timu village.